Legal uncertainty of the arrangement for the implementation of foreclosed collateral (ayda) through auction - Miftahul Ulum; Aad Rusyad Nurdin (IHSA Institute, 2023)
Foreclosed Collateral or Ayda is one of the instruments in the settlement of bad loans that can be used by the Bank. However, there are overlaps in the implementing regulations which result in legal uncertainty for the Bank when it chooses this method. In the banking law, the Bank is prohibited from owning Ayda and must be resold as soon as possible within one year so that the proceeds from the sale of Ayda can be immediately utilized by the Bank but in the auction regulations and land registration regulations the Bank is determined as the owner of Ayda if within one period the Bank does not may appoint other parties as buyers. Uncertainty regarding Ayda implementation arrangements after the oneyear period has passed has an impact on the large costs and taxes that must be borne by the Bank.